Electrocoagulation using Aluminium and Stainless Steel Electrodes for the Removal of Turbidity, Colour and Suspended Solids from Full-Handwashing Car Wash Wastewater - Asmadi, Anwari Khazim; Ab Aziz, Nur Adila (Journal of Advancement in Environmental Solution and Resource Recovery, 2021)
The increasing demand for carwash services in Malaysia has become one of the contributors to the release of untreated carwash wastewater into water bodies which adversely impact the environment, especially the aquatic life. The objective of this study is to investigate the effectiveness of electrocoagulation in treating turbidity, suspended solids and colour from the carwash wastewater which has been collected from Ijan Car Wash Station in Parit Raja. This treatment has been conducted by using aluminium and stainless steel as the electrodes in a monopolar electrode configuration. The optimum conditions for electrocoagulation such as current density, retention time, and initial pH have been determined based on its performance in reducing turbidity, suspended solids, and colour. The range of the tested current density was 27 - 82 A/m2, 10 until 120 minutes electrolysis time and initial pH from 6 to 10. The electrode distance and settling time were kept constant 5 cm and 30 minutes respectively. The result shows that the optimum condition for electrocoagulation process of Al-St electrode pair was determined at the current density of 27 A/m2, electrolysis time of 110 minutes, and the initial pH of 8 which has removal efficiencies of the turbidity, colour and suspended solid of 90.3 %, 88.12 % and 94.27 % respectively. The electrocoagulation process also has the potential to be utilized in removing physical properties of car wash wastewater based on its effective removal, especially turbidity, suspended solids and colour. For the future work, reduces in terms of spacing between electrodes and increase the total working area of electrodes could give more effect for the removal efficiencies.